Análisis, diseño e implementación de una aplicación web para comunicación y control de un prototipo de control domótico en una plataforma de hardware Arduino en las instalaciones de la empresa ATEC de la ciudad e Machala. - Luna Romero, Zayda Ines (2014)
This work was done for the company ATEC city of Machala, is a company that provides its electrical and electronic professional services, also has equipment and materials to end services it offers, both for internal use and for marketing. The project was carried out in order to create a prototype of automation control and develop a web application for communication and control it using free software and hardware, to optimize the use of energy resources and ensure the integrity of staff and facilities the company.